2017
DOI: 10.1016/j.cmi.2017.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Group B streptococcal colonization and transmission dynamics in pregnant women and their newborns in Nigeria: implications for prevention strategies

Abstract: These data demonstrate high rates of colonization and transmission in a population that does not use antibiotics to prevent neonatal infections, a strategy that should be considered in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 23 publications
5
42
1
Order By: Relevance
“…GBS was isolated more frequently in young women (aged ≤ 30 years) compared to older women. Similar findings were reported by other authors [20,21].…”
Section: Discussionsupporting
confidence: 93%
“…GBS was isolated more frequently in young women (aged ≤ 30 years) compared to older women. Similar findings were reported by other authors [20,21].…”
Section: Discussionsupporting
confidence: 93%
“…The volume of blood collected for culture was reported by 11 studies obtained at least 1 ml of blood from the neonates. One of these studies used new-born weight to determine the volume of blood to collect for culture[ 25 ]. Overall blood culture yield across all studies was 24.5% but ranged from 20% [ 27 ] to 56% [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two of the studies were single center studies carried out in tertiary hospitals. Two studies were done in multiple hospitals: one in three and the other in four hospitals[ 25 , 49 ]. Two studies were carried out at different times in the same rural area while all others were in urban areas[ 27 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…GBS remains the most common pathogen causing bacterial meningitis in young infants <3 months old ( 3 , 31 ). Several studies have documented that intrapartum antibiotic prophylaxis in pregnant women with GBS colonization has lowered the incidence rate of GBS early-onset disease; however, this has no significant effect on GBS late-onset disease ( 32 , 33 ). In our cohort, GBS accounted for more than half of bacterial meningitis cases, mostly presented as late-onset disease (33 cases, 84.6%) and our previous studies found that more than half of GBS invasive disease cases in the neonatal intensive care unit cause meningitis ( 34 ).…”
Section: Discussionmentioning
confidence: 99%